2019
DOI: 10.1080/00288330.2018.1562945
|View full text |Cite
|
Sign up to set email alerts
|

Ocean temperature change around New Zealand over the last 36 years

Abstract: Ocean temperature changes around New Zealand are estimated from satellite sea surface temperature (SST) products since 1981, two high resolution expendable bathythermograph transects (HRXBT) since 1986 and 1991, and Argo data since 2006. The datasets agree well where they overlap. Significant surface warming is found in subtropical waters. Greatest warming is east of Australia and in the central Pacific. All NZ coastal waters are warming, with strongest warming east of Wairarapa and weakest between East Cape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 32 publications
8
42
0
Order By: Relevance
“…The southern hemisphere SST 1982-2020 trend (Figure 1a) is consistent with trends for similar periods published elsewhere (e.g. Bulgin et al, 2020;Sutton & Bowen, 2019). Highest warming occurred off south-eastern Australia, South America, South Africa, and in the central South Pacific Ocean.…”
Section: Resultssupporting
confidence: 89%
“…The southern hemisphere SST 1982-2020 trend (Figure 1a) is consistent with trends for similar periods published elsewhere (e.g. Bulgin et al, 2020;Sutton & Bowen, 2019). Highest warming occurred off south-eastern Australia, South America, South Africa, and in the central South Pacific Ocean.…”
Section: Resultssupporting
confidence: 89%
“…It is worth noting that modeled ocean heat content over the last few years is lower than it has been in the past (i.e., 1989, 1999-2001), which would imply that MHWs have not been as intense as they could have been. However, with SSTs and heat content showing an upward trend over the last decades in the Tasman Sea (Roemmich et al, 2015;Sutton and Bowen, 2019), we could soon reach those higher heat content values again, resulting in more intense MHWs. Figures 7, 10 show large interannual to decadal variability.…”
Section: Heat Content and Mhwmentioning
confidence: 88%
“…The difference between air and sea surface temperatures (SST) predominantly controls the air-sea exchange of heat and moisture, which is central to weather and climate. As this region warms (Sutton and Bowen, 2019), it will be vulnerable to experiencing more frequent and more intense extreme events, such as marine heatwaves (MHWs) and tropical storms (Kuleshov et al, 2008;Oliver et al, 2017Oliver et al, , 2018a. Recent studies have shown how MHWs influence the regional climate, terrestrial temperatures, rainfall patterns and ecosystems of Australia, New Zealand and the Pacific Islands (Johnson et al, 2011;Swart and Fyfe, 2012;Purich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…New Zealand has a small land mass, and air temperatures are highly correlated with ocean temperatures, although interannual variability occurs due to the El Nino/Southern Oscillation [103]. Rising sea temperatures are of concern and raised averaged sea surface temperatures have now been recorded for some years [104,105]. In the austral summer of 2017/2018, sea surface temperature anomalies reached +3.7 • C in the eastern Tasman Sea, exacerbated by reduced upper ocean mixing [29].…”
Section: Potential Impacts Of Climate Changementioning
confidence: 99%
“…A long-term study of overlapping datasets compiled since 1981, with datasets showing good agreement, indicate significant surface warming of subtropical waters over that time. The greatest warming was to the west of New Zealand (east of Australia) and in the central Pacific, but all New Zealand coastal waters are warming [104] and this will favour Gambierdiscus and Fukuyoa growth.…”
Section: Potential Impacts Of Climate Changementioning
confidence: 99%